Asymmetric Isomer Effects in Benzo[c ][1, 2, 5]thiadiazole‐Fused Nonacyclic Acceptors: Dielectric Constant and Molecular Crystallinity Control for Significant Photovoltaic Performance Enhancement. (25th June 2021) - Gao, Wei; Fan, Baobing; Qi, Feng; Lin, Francis; Sun, Rui; Xia, Xinxin; Gao, Jinhua; Zhong, Cheng; Lu, Xinhui; Min, Jie; Zhang, Fujun; Zhu, Zonglong; et al.
Abstract: Herein, asymmetric isomer effects are systematically explored by designing and synthesizing two benzo[ c ][1, 2, 5]thiadiazole (BT)‐fused nonacyclic electron acceptors. By changing from BP6T‐4F to asymmetric ABP6T‐4F, significantly enhanced dielectric constant and inhibited excessive molecular aggregation and unfavorable edge‐on orientation could be achieved. The reduced exciton binding energy also facilitates a more efficient dissociation process in PM6:ABP6T‐4F compared to PM6:BP6T‐4F with the same energy offset. Moreover, the weaker crystallization behavior enables a significantly enhanced miscibility between PM6 and ABP6T‐4F than that between PM6 and BP6T‐4F, which leads to an optimized micromorphology with smooth surface, suitable domain size, and ordered π–π stacking. Organic solar cells (OSCs) based on PM6:ABP6T‐4F achieve a 15.8% power conversion efficiency (PCE), which is remarkably higher than that of PM6:BP6T‐4F‐based OSCs (6.4%). Furthermore, ternary devices are also fabricated considering good compatibility between ABP6T‐4F and CH1007 to deliver a PCE over 17%. This study reveals the effectiveness and great potential of asymmetric isomerization strategy in regulating molecular properties, which will provide guidance for the future design of non‐fullerene acceptors. Abstract : Asymmetric isomerization from BP6T‐4F to ABP6T‐4F not only lowers the exciton bonding energy but also optimizes the crystallization performance, achieving a pronounced isomer effect with 9.4% power conversion efficiency enhancement. Moreover, ternary devices are also fabricated, considering good compatibility between ABP6T‐4F and CH1007, to deliver a power conversion efficiency over 17%.